Clinicopathological features of PD-L1 protein expression, EBV positivity, and MSI status in patients with advanced gastric and esophagogastric junction adenocarcinoma in Japan. Issue 1 (31st December 2022) - Yoshida, Tsutomu; Ogura, Go; Tanabe, Mikiko; Hayashi, Takuo; Ohbayashi, Chiho; Azuma, Mizutomo; Kunisaki, Chikara; Akazawa, Yoichi; Ozawa, Soji; Matsumoto, Sohei; Suzuki, Takayoshi; Mitoro, Akira; et al.
ABSTRACT: This real-world study examined the prevalence of programmed death ligand-1 (PD-L1) expression and assessed the frequency of microsatellite instability-high (MSI-H) status and Epstein-Barr virus (EBV) positivity in Japanese patients with advanced gastric and gastroesophageal junction (GEJ) adenocarcinoma. This multicenter (5 sites), retrospective, observational study (November 2018–March 2019) evaluated Japanese patients with advanced gastric and GEJ adenocarcinoma after surgical resection (Stage II/III at initial diagnosis) or unresectable advanced cancer (Stage IV). The primary objectives were prevalence of PD-L1 expression (combined positive score [CPS] ≥1), MSI status, and EBV positivity. Tumor specimens of 389/391 patients were analyzed (male, 67.1%; mean age, 67.6 ± 12.2 years); 241/389 (62%) were PD-L1 positive, 24/379 (6.3%) had MSI-H tumors, and 13/389 (3.3%) were EBV positive. PD-L1 expression was higher in tumor-infiltrating immune cells than in tumor cells for lower CPS cutoffs. Among patients with MSI-H tumors and EBV-positive tumors, 19/24 (79.2%) and 9/13 (69.2%), respectively, were PD-L1 positive. A greater proportion of patients with MSI-H tumors (83.3% [20/24]) were PD-L1 positive than those with MSI-low/stable tumors (60.8% [216/355]; p = .0297); similarly, an association was observed between history of H pylori infection and PD-L1 expression. A higher proportion of patients with MSI-H tumors demonstrated PD-L1 expression with a CPS ≥10 (66.7% [16/24]) vs those with MSI-low/stable tumors (24.8% [88/355]; p < .0001). The prevalence of PD-L1 positivity among Japanese patients was comparable to that in previous pembrolizumab clinical trials and studies in gastric cancer. Particularly, higher PD-L1 expression was observed in MSI-H tumors.